An Analysis of Government Actions for the Protection and Recovery of Forest-dwelling Woodland Caribou (Rangifer tarandus caribou) in Ontario, Canada - Wilkinson, Christopher J.A. (Rangifer, 2010)
The Government of Ontario has legal responsibilities to protect and recover the province’s population of forest-dwelling woodland caribou, which is classified as a threatened species. Loss and fragmentation of habitat caused by commercial timber harvesting, land clearing, and linear disturbances such as road building have resulted in range recession. Ontario’s Woodland Caribou Conservation Plan (2009) serves as the provincial government’s response to a recovery strategy. This paper contends that the likelihood of success for this conservation plan is low as it focuses on mitigating rather than eliminating threats, relies on the unproven and circumspect hypothesis that woodland caribou will re-occupy logged habitat, and lacks clarity and details on implementation. Sound government action focused on protection and recovery is needed to prevent the imperilment and extirpation of this species at risk.